Dr. Mohd Azraai unveils LUNAS: The future of AI-Powered Aquaculture - Nur Hartini, Mohd Hatta (UMPSA, 2025)
PEKAN, 14 July 2025 – In a bid to enhance efficiency and accuracy in fish monitoring, Dr. Mohd Azraai Mohd Razman, a lecturer from the Faculty of Manufacturing Engineering Technology and Mechatronics (FTKPM), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), has developed an AI-based automatic fish monitoring system called the Live Underwater Aquaculture System (LUNAS) — a breakthrough innovation poised to transform Malaysia’s aquaculture industry.